A systematic review of social network methods in high impact developmental psychology journals. Issue 4 (11th February 2020) - Neal, Jennifer Watling
Abstract: Although researchers have collected social network data to characterize childhood and adolescent relationships since the 1930s, an expansion of social network analytic techniques has led to the rapid growth of social network data collection in the field of developmental psychology. Despite this growth, reflection on social network methods in developmental psychology has not kept pace. This systematic review aims to understand how articles published in the most visible journals in developmental psychology have collected and analyzed social network data with the goal of critically evaluating these methods to move the field forward. Specifically, after screening 787 articles drawn from a systematic search of the 30 journals with the highest impact factors in developmental psychology, 201 empirical articles employing social network analysis were reviewed. Findings focus on where social network data are collected, who social network data are collected on, what types of social network relationships are collected, and how social network data are collected and analyzed. Review results are used to highlight potential gaps in social network methods as well as the implications of these gaps for understanding developmental processes and to identify recommendations for future social network studies in developmental psychology.